Investigation of heat transfer in wavy and dual wavy micro-channel heat sink using alumina nanoparticles. (December 2021) - Khan, Muhammad Zia Ullah; Younis, M. Yamin; Akram, Naveed; Akbar, Bilal; Rajput, Umair Ahmed; Bhutta, Rumeel Ahmad; Uddin, Emad; Jamil, Muhammad Ahsan; García Márquez, Fausto Pedro; Zahid, Fahad Bin
Abstract: Thermal management is crucial for the proper functioning of a system whether it is in electronics, process industry, automobile, and renewable devices. Micro-channel heat exchanger has proved to be efficient in heat ejection from renewable systems due to high heat transfer surface to volume ratio. This study focuses on evaluating the cooling performance of straight, wavy, and dual wavy Micro-Channel Heat Exchanger by modelling the heat transfer model in ANSYS Fluent. The incompressible fluid is considered in the laminar regime using alumina-based nanofluids with 1%, 3%, and 6% concentration. The solution is computed by selecting SIMPLE pressure-velocity coupling scheme with second-order momentum and energy discretization. Nusselt number, pressure drop, base temperature, and Thermal Performance Factor (TPF) are used as performance parameters for comparing nanofluids performance at Reynolds number range of 100–900. For straight, wavy, and dual wavy model heat transfer, as well as pressure drop, increased with Reynolds number. It is observed that wavy and dual wavy channels compared to straight channel improved convective heat transfer due to the formation of secondary vortices at the curved section. Dual wavy with wavy base and flat base wall showed highest Nusselt number increase of more than double when compared with straight channel of equal concentration. For 6% nano particles addition in all channels, on average both dual wavy channels showed highest improvement of 8% when compared with 0% concentration channel. Dual wavy channel with a flat base and wavy base reduced the base heater temperature by 10 °C and 9 °C compared to the straight channel. A maximum Thermal Performance Factor of 2.2 is achieved for dual wavy channel with a wavy base configuration with 6% nanoparticles. Highlights: The effect of geometry and nanoparticles concentrations on the heat transfer and friction factor of the microchannel. The conventional straight channel is compared with uniform wavy, dual wavy channel considering the equal volume. The optimum channel is identified by using the Thermal Performance Factor considering the effect of heat transfer and pressure drop. The heat transfer performance of all wavy channels was more than double compared to straight channel and increased with an increase in Reynolds number. The base wall temperature reduced on average from 6 °C to 10 °C for a 100 to 900 increase in Reynolds number compared to the straight channel.